Refrigeration Requirements for Precooling and Fermentation Control in Wine Making - le Roux, J.M.W.; Purchas, Katy; Nell, B. (South African Journal of Enology and Viticulture, 2017)
A database is provided which can be used as a guide to determine the maximum refrigeration capacity required during wine making (precooling and fermentation control). Factors such as maximum daily grape intake, temperature of the grapes, precooling period, fermentation rate, heat gain in the fermentation building, heat gain in the refrigerated water distribution system as well as the efficiency of refrigeration systems are considered. Graphs, as well as equations, are provided from which the maximum refrigeration capacity required for grape intakes varying from 25 t - 1 000 t per day can be determined in kJ/h. Provision is made for three different precooling periods. Separate graphs are provided from which the influence of the temperature of the grapes, as well as the influence of heat gain in refrigerated water distribution systems on the overall refrigeration capacity required, can be determined respectively. The database cannot replace thorough detailed refrigeration system design and engineering. However, it provides wine makers with a simple guide whereby designs can be checked, or the use of the capacity of existing systems managed more effectively.